PENGARUH PELATIHAN DAN KERJA TERHADAP KINERJA KARYAWAN PADA PT HUTAN RINDANG BANUA KECAMATAN SUNGAI LOBAN KABUPATEN TANAH BUMBU - Abdul Kadir Ms Kadir; Noorlaily Maulida; Siti Mardah (Jurnal Ilmu Ekonomi dan Bisnis, 2022)
ABSTRACT The Effect of Job Training on Employee Performance in PT Hutan Rindang Banua in Sungai Loban Tanah Bumbu This study aims to test: (1) know the description of job training and employee performance at PT Hutan Rindang Banua in Sungai Loban Tanah Bumbu, (2) knows that job training has an impact on employee performance at PT. Hutan Rindang Banua in Tanah Bumbu. The design of this research is quantitative research and is a survey research, where data is obtained questionnaire. Research sample is 35 employees of PT Hutan Rindang Banua with simple linear regression data analysis. The results showed that: 1) There was a partial effect of job training on employee performance at PT. Banua Shady Forest, Sungai Loban District, Tanah Bumbu Regency (0.000 < 0.05). 2) There is a partial effect of motivation on employee performance at PT Hutan Rindang Banua, Sungai Loban District, Tanah Bumbu Regency (0.000 < 0.05). 3) There is a simultaneous effect of job training and motivation on employee performance at PT. Banua Shady Forest, Sungai Loban District, Tanah Bumbu Regency (0.000 < 0.05). Suggestions that can be recommended are the need for standardization and adjustment of the training period to the ability of the workforce to receive training materials, preferably for workers who excel are given training and motivation by way of promotions and incentives so as to increase their motivation and performance. Keywords: Job Training, Employee Performance